Effectiveness of red gypsum as cement replacement on foam concrete properties (RGFC) - Ying Yong, Voon (2014)
The goal of this study is to assess the possibilities of incorporating red gypsum in production of foamed concrete. Invention of lightweight composite design and construction utilizes existing technology which has become an alternative choice in current markets to make construction project getting easier and faster. The reuse of red gypsum waste is the areas where great opportunity exists for cost saving in the construction industry red gypsum as cement replacement in foam concrete in different percentage show improvement in the development of strength. In water and air curing condition, it shows that the samples in water curing possess higher strength compare to the air curing samples. But the strength achieved by RGFC was still lower than the control foam concrete. By comparing to four mixes, the strength of the lower percentage RG was higher than higher percentage of RG. This can be concluded that 5% was not capable to be use but there maybe some condition that needed for this type of concrete.